Working with special populations - Jarvis, M.; Moody, J. (Strength and conditioning for sports performance, 2016)
The UK boasts a strong tradition of supporting and driving forward sports performance in disabled athletes. The Paralympic movement itself began in the UK at Stoke Mandeville in 1948 as a competition for Second World War veterans with spinal column injuries. At this time sports participation was primarily used as a therapy to restore both physical strength and confidence. Since this time great progress has been made in Paralympic sport, and international competition is intense across a wide range of sports. In the UK, Paralympic athletes work within support programmes and networks in the same way as their able-bodied colleagues. Consequently, strength and conditioning (S&C) coaches in the UK have both the opportunity and the responsibility to drive S&C for Paralympic athletes forward to new levels of understanding. The commitment of the UK Strength and Conditioning Association (UKSCA) to this is reflected in Paralympic scenarios being used in some UKSCA accreditation processes. This text is not intended to serve as a definitive resource on the medical nature of disability. Rather, this is a practical guide which may serve as a starting point for coaches new to Paralvmpic S&C. The S&C coach should draw confidence from attaining a basic understanding of what he/she will face with each athlete and some practical examples from real life. It can be argued that the challenge of Paralvmpic S&C demands a greater depth of thought and problem solving than for able-bodied training, owing to the highly individual nature of disability. Aspiring coaches should not be daunted by this task. Indeed, many feel that working with disabled athletes should be part of the education of all S&C coaches, as it allows for the honing of these critical core skills. As the `easy option` of generic programming, which is based solely on the sport and ignores the individual (a common flaw in junior coaches), is not available, the coach must instead engage in the triangular thinking which underpins all good programming (see Figure 20.1). The wide range of classifications within various Paralympic events is evidence of the highly diverse nature of disability. Even within the same class, significant differences will still exist. Consequently the S&C coach must experiment to produce bespoke solutions to highly individual problems, and it is critical that this is done in conjunction with the athlete. If you are not used to working with disabled athletes it is very easy to allow an athlete`s disability to become `the elephant in the room`. Naturally, the Paralympic athlete wants to be viewed primarily as an athlete, rather than the focus being on his/her disability. However, talking about what the athlete can and can`t do openly will result in the two of you quickly co-creating novel solutions to problems and will significantly improve the impact of your programming. It will also put both of you at much greater ease. A potential barrier to some S&C coaches engaging with disabled athletes is the fear of a lack of knowledge. It is hoped that this text will provide a useful starting point in such situations. However, the fear should never be prohibitive. When presented with an athlete from a new sport which they had not previously encountered, most coaches would relish the challenge. They would most likely do as much research as they could about the demands of the sport and gain further information from the athlete. The Paralympic challenge is no different other than that the unfamiliar comes from a different comer of our triangular thought process.